Productivity and economic efficiency of winter wheat (Triticum aestivum L.) cultivation depending on preceding crops and sowing dates - Umrykhin, N.; Sokolovska, I.; Mashchenko, Yu. (International Journal of Agricultural Technology, 2024)
It was found that the most effective factor influencing yield indicators was preceding crop, with increased in winter wheat grain yield of 1.23 t ha-1 for soybean as a predecessor in favorable years and +0.71 t ha-1 in other years. In unfavorable years for the crop, delaying the sowing dates of winter wheat did not significantly affect grain yields when grown after sunflower, while after soybean as preceding crop, a significant yield increase was observed, ranging from 5.14 to 5.47 t ha-1. Late sowing dates in optimal vegetative conditions led to decrease in crop yield, especially affected soybean as preceding crop: -0.64 t ha-1 and -1.12 t ha-1. It is advised to sow winter wheat on September 15th after sunflower and on September to 15th trom 30th after soybean as preceding crop. The research results indicated a significantly increased in productivity of winter wheat after soybean compared to sunflower as preceding crop, regardless of the sowing date. The yield of grain units from the main and by-products of winter wheat averaged 11.66 t ha-1 after soybean as preceding crop and 9.78 t ha-1 after sunflower; feed units were 10.05 t ha-1 and 8.43 t ha-1, digestible protein units were 1.97 t ha-1 and 1.65 t ha-1, respectively. The yield increased in grain units after soybean preceding crop ranged from 1.61 to 2.15 t ha-1; feed units – 1.39-1.85 t ha-1; digestible protein units – 0.27-0.36 t ha-1. Delaying the sowing dates of winter wheat to later dates had a negative impact on crop productivity, with the most significantly decreased which observed after sunflower as a predecessor. Higher economic indicators were achieved when growing winter wheat after soybean and sowing on September 15: the value of the produced goods increased to 33540 UAH ha-1, net profit reached 15489 UAH ha-1 with profitability of 85.8 %.